2020
DOI: 10.1002/ldr.3654
|View full text |Cite
|
Sign up to set email alerts
|

Usage ofMODIS NDVIto evaluate the effect of soil and water conservation measures on vegetation in Burkina Faso

Abstract: The dramatic droughts in West Africa from the 1960s to the 1990s compelled Burkina Faso to implement soil and water conservation (SWC) measures in the late 1970s.The purpose was to combat land degradation (e.g., desertification) in areas that experienced a decrease in vegetation productivity. In this study, normalized difference vegetation index (NDVI) trends from 2002 to 2016 were analyzed using the Mann-Kendall test to explore the spatio-temporal variations of vegetation at SWC and non-SWC sites in selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…These in turn have implications for strategies toward sustainable development, managing negative impacts of climate change on different ecosystems and their service provision to local communities and wider issues of maintaining biodiversity and reducing soil erosion, amongst others [20,51,81]. This is important because some ecosystems can maintain their existing services or even enhance their future service provision under appropriate management strategies [5,26].…”
Section: Implications For Climate Change Land Degradation and Sustainable Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…These in turn have implications for strategies toward sustainable development, managing negative impacts of climate change on different ecosystems and their service provision to local communities and wider issues of maintaining biodiversity and reducing soil erosion, amongst others [20,51,81]. This is important because some ecosystems can maintain their existing services or even enhance their future service provision under appropriate management strategies [5,26].…”
Section: Implications For Climate Change Land Degradation and Sustainable Developmentmentioning
confidence: 99%
“…degradation [18,[24][25][26]. The advantage of remote sensing approaches is that changes over larger areas can be identified more easily, consistently and with the same resolution or error, which cannot be achieved in field studies, especially in remote locations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study used GIM-TR to analyze vegetation change in a relatively small study area [25], but its results showed that GIMMS NDVI was too coarse to detect enough breakpoints by BFAST, which would lead to an underestimation of the vegetation decrease. However, data from a new generation of satellites, namely Moderate Resolution Imaging Spectroradiometer (MODIS) NDVI data, with a higher resolution (i.e., 250 m, 500m and 1000m) is more commonly used to detect the vegetation change in small study areas [26][27][28]. In addition to MODIS NDVI, the NDVI calculated from Landsat data with higher resolution (i.e., 30 m) was also used to detect vegetation change in small area.…”
Section: Introductionmentioning
confidence: 99%